"Building Bridges of Justice: Restorative Justice Reconstruction with The Indonesian Criminal System After Law No. 1 Of 2023" - Padlah Riyadi (Journal of Law and Humanities Review, 2025)
In the context of criminal law reform in Indonesia through the new Criminal Code (KUHP) accommodates and includes the principle of Restorative Justice, where the formulation of types of criminal acts (strafmaat) contains restorative properties. So it is very possible that the concept of Restorative Justice can be used as part of the reform of criminal law in Indonesia in the future. Discussion, ratification, and implementation of the draft Criminal Code in accordance with Indonesian values, considering that the current Criminal Code is no longer suitable for the culture of the Indonesian nation which is based on Customary Law (traditional law) and other values ??of diversity. This research is a normative legal research. In normative legal research, law is conceptualized as what is written in laws and regulations (law in books) or law is associated with conceptualizing it as a rule or norm that is a benchmark for behavior. In normative research, the data sources used are only secondary data, consisting of primary legal materials, secondary legal materials or tertiary legal materials related to Restorative Justice, The results of this study are:The implications of Restorative Justice after the ratification of the RKUHP into the Criminal Code Law from the perspective of just law, namely the substance of Restorative Justice has actually been facilitated in the Criminal Code Law and is spread across various articles. One of these articles is Article 51 of the Criminal Code Law which relates to the purpose of punishment which from the perspective of just and human-dignifying law is relevant to re-educate prisoners and is linear with the divine value that requires the concept of repentance nasuha' where the all-forgiving attitude possessed by God is the basis that even humans who behave badly can change to a better path. In addition, Article 52 of the Criminal Code Law emphasizes that punishment must not degrade human dignity, which means that maintaining human dignity is God's command and people who ignore the dignity of fellow human beings are people who go beyond the limit. Thus, it can be concluded that the substance of restorative justice that has been facilitated in the Criminal Code Law, articles 51, 52, 53, 54 and specifically Article 132, which states that the authority to prosecute is declared null and void if there has been a settlement outside the judicial process, is in fact relevant to the idea and purpose of the law itself.